Guanidyl modification of the 1-azabicyclo[3.1.0]hexane ring in ficellomycin essential for its biological activity. Issue 27 (25th June 2020) - Kurosawa, Sumire; Matsuda, Kenichi; Hasebe, Fumihito; Shiraishi, Taro; Shin-ya, Kazuo; Kuzuyama, Tomohisa; Nishiyama, Makoto
Abstract : The guanidyl unit essential for the activity of ficellomycin is attached to the 1-azabicyclo[3.1.0]hexane ring-containing amino acid via a novel inter ω–ω aminotransferase. Abstract : The 1-azabicyclo[3.1.0]hexane ring is a key moiety in natural products for biological activities against bacteria, fungi, and tumor through DNA alkylation. Ficellomycin is a dipeptide that consists of l -valine and a non-proteinogenic amino acid with the 1-azabicyclo[3.1.0]hexane ring structure. Although the biosynthetic gene cluster of ficellomycin has been identified, the biosynthetic pathway currently remains unclear. We herein report the final stage of ficellomycin biosynthesis involving ring modifications and successive dipeptide formation. After the ring is formed, the hydroxy group of the ring is converted into the guanidyl unit by three enzymes, which include an aminotransferase with a novel inter ω–ω amino-transferring activity. In the last step, the resulting 1-azabicyclo[3.1.0]hexane ring-containing amino acid is connected with l -valine by an amino acid ligase to yield ficellomycin. The present study revealed a new machinery that expands the structural and biological diversities of natural products.